ANALISIS KORELASI MODEL PEMBELAJARAN DENGAN TEKNOLOGI KOMUNIKASI DI SMK MUHAMMADIYAH BULUKUMBA - Muh. Nasrum (Jurnal Pendidikan Sang Surya, 2023)
Correlation Analysis of Learning Models with Communication Technology at Muhammadiyah Bulukumba Vocational School. This type of research is descriptive research, namely describing the learning process based on communication technology, which aims to determine the relationship between variable X and variable Y or the correlation of learning models with communication technology. The population in this study was 39 students, consisting of 21 students in class XII of the Nursing Department and 18 students in class XII of the Computer and Network Engineering Department, Bulukumba Muhammadiyah Vocational School. Sampling in this study used a saturated sampling technique, meaning the population was the same as the sample size, namely 40 students. Data was collected using observation techniques, questionnaires and interviews. The data was analyzed using the Product Moment correlation data analysis technique. The research results show that based on a significance level of 5% and N = 39, it turns out that the Ho rejection limit in the r table is 0.257. The calculated r xy value = 0.762 turns out to be > from the r xy table = 0.257, so the calculated r xy value is significant, so Ho is rejected and H1 is accepted, meaning that there is a correlation between learning models and communication technology at Muhammadiyah Bulukumba Vocational School.